Implementation of selected preventive examinations by students of the Medical University of Warsaw - Staniszewska, Anna; Nidzgorska-Cichońska, Magdalena; Olejniczak, Dominik (Journal of Education, Health and Sport, 2019)
Aim: Determination of frequency of performing preventive examinations by students of Medical University of Warsaw. Materials & Methods: Study was carried use of an original survey questionnaire, on group of 1000 students of Medical University of Warsaw, in period 03.2018-12.2018. Results: Among respondents dominated: women (73%), aged 19-25, studying public health (68%). Conclusion: Depending on type of examination, students performed them at different intervals. The future medical staff should be a model for the general public, the role of prevention should be made known to respondents.